A Perspective on Age Restrictions and Other Harm Reduction Approaches Targeting Youth Online Gambling, Considering Convergences of Gambling and Videogaming - Shi, Jing; Colder Carras, Michelle; Potenza, Marc N.; Turner, Nigel E. (Frontiers in Psychiatry, 2021)
Internet gambling has become a popular activity among some youth. Vulnerable youth may be particularly at risk due to limited harm reduction and enforcement measures. This article explores age restrictions and other harm reduction measures relating to youth and young adult online gambling. A systematic rapid review was conducted by searching eight databases. Additional articles on online gambling (e.g., from references) were later included. To place this perspective into context, articles on adult gambling, land-based gambling, and substance use and other problematic behaviors were also considered. Several studies show promising findings for legally restricting youth from gambling in that such restrictions may reduce the amount of youth gambling and gambling-related harms. However, simply labeling an activity as “age-restricted” may not deter youth from gambling; in some instances, it may generate increased appeal for gambling. Therefore, advertising and warning labels should be examined in conjunction with age restrictions. Recommendations for age enforcement strategies, advertising, education, and warning labels are made to help multiple stakeholders including policymakers and public health officials internationally. Age restrictions in online gambling should consider multiple populations including youth and young adults. Prevention and harm reduction in gambling should examine how age restriction strategies may affect problem gambling and how they may be best enforced across gambling platforms. More research is needed to protect youth with respect to online gambling.